Neopterin level in the anterior segment of the eye in induced uveitis with ocular hypertension when treated by dipeptide carnosine (Ukrainian Journal of Ophthalmology, 2025)
Background: We have previously demonstrated that the course of inflammatory process was significantly more severe in eyes with anterior uveitis with ocular hypertension (OHT) than in those with anterior uveitis with normal intraocular pressure (IOP), which was largely due to a more marked activation of enzymes producing active oxygen as well as peroxidative processes in uveal structures of experimental animals. Aside from oxidative stress characteristics, our attention has been drawn to neopterin as a potential marker of inflammation severity and the efficacy of inflammation control. Because there is a paucity of reports focused on the potential for using this characteristic as a diagnostic criterion in ocular disorders, especially in uveitis with raised IOP, studies on this subject are important.Purpose: To assess the impact of dipeptide carnosine on the level of neopterin in the rabbit’s anterior eye segment in anterior uveitis with ocular hypertension. Material and Methods: Forty-four Chinchilla rabbits (88 eyes) were divided into 4 experimental groups (group 1, 10 animals with induced OHT only; group 2, 10 animals with induced experimental non-infectious uveitis only; group 3, 12 animals with OHT induced prior to experimental non-infectious uveitis; group 4, 12 animals treated with carnosine for experimental uveitis with OHT). Rabbits of group 4 received 5% carnosine solution into the conjunctival sac, twice daily for the four weeks. The control group comprised 9 intact rabbits. Neopterin enzyme-linked immunosorbent assay kit was used to determine neopterin levels in uveal tract tissue, aqueous humor and tear samples according to the manufacturer’s instructions. Statistica 5.5 (StatSoft, Tulsa, OK, USA) software and parametric statistical tests were used for statistical analysis.Results: Neopterin levels in uveal tract tissue, aqueous humor and tear samples taken from rabbit’s eyes with induced OHT only were increased compared to controls but lower than those in non-infectious uveitis only. Neopterin levels in uveal tract tissue, aqueous humor and tear samples from rabbit’s eyes with induced both anterior uveitis and OHT (group 3) were 5.2-, 3.7- and 2.4 times higher, respectively, than in controls, and 42.5% (р < 0.05), 28.5% (р < 0.05) and 23.6% (р < 0.05) higher, respectively, than in samples taken from rabbit’s eyes of group 2. The carnosine treatment of induced both anterior uveitis and OHT (group 4) contributed to reduced levels of neopterin is samples under study, with neopterin levels in uveal tract tissue, aqueous humor and tear fluid being 39.4%, 38.9% and 30.2% lower, respectively, than in samples taken from rabbit’s eyes of group 3 (anterior uveitis plus OHT without treatment) (р < 0.01), and 3.2-, 2.2- and 1.7 times higher, respectively, than in controls (р < 0.001).Conclusion: High neopterin levels in the uveal tract tissues and anterior chamber aqueous fluid indicated its impact on the course of inflammation in animals with induced uveitis only and especially in those with induced both uveitis and OHT. A high neopterin level in the tear fluid in anterior uveitis can be considered a diagnostic marker of the severity of inflammation in the anterior segment of the eye. The carnosine treatment statistically significantly reduced neopterin levels in the uveal tract tissues, anterior chamber aqueous fluid and tear fluid in rabbit’s eyes with induced both uveitis and OHT. The changes in neopterin levels were caused by a reduction in the severity of inflammation in the anterior segment of the eye.
Keywords: non-infectious uveitis; ocular hypertension; neopterin; carnosine; rabbits